2016
DOI: 10.1186/s41240-016-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of phospholipase C β1 in olive flounder (Paralichthys olivaceus) following external stress stimulation

Abstract: In this study, to clarify the function of PoPLC-β1, in response to stress challenge, we examined the PoPLC-β1 expression pattern in response to external stress (pathogen-associated molecular pathogen challenge and environmental challenge including temperature and salinity). PoPLC-β1 expression analysis of tissue from olive flounder showed that the messenger RNA (mRNA) was predominantly expressed in the brain, heart, eye, liver, spleen, and stomach. We also tested the mRNA expression of the PoPLC-β1 in the sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…High mortality and low growth rates were usually observed in the areas above possibly due to the salinity stress. It was previously revealed that the physiological state of crustaceans could be altered by high or low salinity stress (Long et al, 2018; Schmitz et al, 2016; Woo et al, 2016). Salinity stress is characterized by an increased inflammatory response and decreased antioxidant capacity in a variety of aquatic animals.…”
Section: Introductionmentioning
confidence: 99%
“…High mortality and low growth rates were usually observed in the areas above possibly due to the salinity stress. It was previously revealed that the physiological state of crustaceans could be altered by high or low salinity stress (Long et al, 2018; Schmitz et al, 2016; Woo et al, 2016). Salinity stress is characterized by an increased inflammatory response and decreased antioxidant capacity in a variety of aquatic animals.…”
Section: Introductionmentioning
confidence: 99%